2017
DOI: 10.1093/ecco-jcc/jjx002.678
|View full text |Cite
|
Sign up to set email alerts
|

P554 Impact of real world home based remote monitoring on quality of care and quality of life in inflammatory bowel disease patients: one year results of pragmatic randomized trial

Abstract: S362Poster presentations the time of initial seton placement), intermediate-term (<12 months from the time of initial seton placement), and long-term (>12 months from the time of initial seton placement) outcomes were analyzed. Results: The study cohort included 41 patients. Indication for placement of draining seton alone rather than definitive surgical fistula repair was presence of anal ulceration, stenosis and/or proctitis (n=30; 73%), complex fistulae not amenable to surgical repair (n=8; 26%) or patient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Atreja et al reported the data on use of HealthPROMISE app, a mobile cloud-based platform, in the USA in an abstract form. 44 The app recorded the QoL and symptom scores which could be tracked by HCPs and alerted them to any worsening.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Atreja et al reported the data on use of HealthPROMISE app, a mobile cloud-based platform, in the USA in an abstract form. 44 The app recorded the QoL and symptom scores which could be tracked by HCPs and alerted them to any worsening.…”
Section: Resultsmentioning
confidence: 99%
“… 34 The HealthPROMISE app study also reported QoL as SIBDQ scores and noted significant improvement in the intervention group [ p -value not reported]. 44 Health-related QoL was measured using the IMPACT questionnaire by Young constant care, home telemonitoring, and telephone consultation studies in paediatric and adolescent patients, and no statistically significant differences were noted between study arms at the end of the follow up in all the three studies. 41 , 42 , 45 , 51 QoL scores at the end of follow up were not available in Carlsen et al ., and hence could not be included in the meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
“…It was demonstrated to modify treatment plans in 25% of patients, and expedited clinic visits in 21.9% of cases. A significant reduction in IBD-related hospitalisations and emergency department visits were noted during the 12-month study period, with quality of life improved in patients using the app [44].…”
Section: Telemedicinementioning
confidence: 90%
“…Table 1 22 23 30 31 32 33 34 35 gives an overview of eHealth tools for IBD that involve patient-provider interaction, with some information about each programme and those currently in development.…”
Section: Ehealth Technology In Ibdmentioning
confidence: 99%
“…Overall QoL started to improve among those randomized to HealthPROMISE within 5 months and was consistently above the control arm through a median 18 months (495 days). 34 The responsiveness of the system is contingent on direct contact with the patient's IBD specialist team.…”
Section: Ehealth Technology In Ibdmentioning
confidence: 99%